The constant term in the expression 1-y² +y is
Answers
Answered by
1
Answer:
We have,
α!β!γ!δ!
8!
(x
2
)
α
(
x
2
1
)
β
(y)
γ
(
y
1
)
δ
α!β!γ!δ!
8!
(x)
2α−2β
×(y)
γ−δ
Forconstantterm
α=β;γ=δ
α+β+γ+δ=8
2α+2γ=8
α+γ=4
(β=1)α=1γ=3(δ=3)
(β=2)α=2γ=2(δ=2)
(β=3)α=3γ=1(δ=1)
(β=4)α=4γ=0(δ=0)
(β=0)α=0γ=4(δ=4)
Constantterm=
1!1!3!3!
8!
+
2!2!2!2!
8!
+
3!3!1!1!
8!
+
4!4!
8!
=2×
6
8×7×6×5×4
+
16
8×7×6×120
+
24
8×7×6×5×4!
×2
=2240+2520+4×7×6
=2240+2520+140
=4900
Answered by
0
Answer:
Step-by-step explanation:
Similar questions